2013
DOI: 10.2478/acs-2013-0040
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the physical-chemical and sensorial properties of Maria type cookies

Abstract: Given the importance of the cookies of type Maria worldwide, and considering the absence of any scientific study setting out their main features, it becomes important to identify the differentiating characteristics of several commercialized brands, in particular related to the chemical, physical and sensory characteristics. In this way, the aim of this work was to study and compare eight different brands of cookies of type Maria. The elemental chemical analysis (moisture, ash, protein, fat, fibre and carbohydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 24 publications
2
45
3
1
Order By: Relevance
“…Hardness in cookies showed values ranging from 33 to 51 N, which were higher to the 15 N observed in cookies added with up to 4.4% of SCG(Hatem et al, 2018), although the hardness of cookies analyzed in this experiment was much lower than the reported byPereira, Correia, and Guiné (2013) in commercial brands of Maria-type cookies, which ranged from 99 to 159 N, and also lower to the 100 N registered in cookies made entirely with wheat flour and baked at 110°C for 10 min(Budžaki et al, 2014). However, cohesiveness and springiness of the cookies are considered low in comparison with cookies made only with wheat flour such as the Maria-type cookies(Pereira et al, 2013) and similar to the found byHatem et al (2018), in cookies made with a lower amount of SCG on them. Textural characteristics found in the cookies made in this experiment could help describe them such as soft, inelastic, and crumbly.…”
contrasting
confidence: 74%
“…Hardness in cookies showed values ranging from 33 to 51 N, which were higher to the 15 N observed in cookies added with up to 4.4% of SCG(Hatem et al, 2018), although the hardness of cookies analyzed in this experiment was much lower than the reported byPereira, Correia, and Guiné (2013) in commercial brands of Maria-type cookies, which ranged from 99 to 159 N, and also lower to the 100 N registered in cookies made entirely with wheat flour and baked at 110°C for 10 min(Budžaki et al, 2014). However, cohesiveness and springiness of the cookies are considered low in comparison with cookies made only with wheat flour such as the Maria-type cookies(Pereira et al, 2013) and similar to the found byHatem et al (2018), in cookies made with a lower amount of SCG on them. Textural characteristics found in the cookies made in this experiment could help describe them such as soft, inelastic, and crumbly.…”
contrasting
confidence: 74%
“…The high protein content increased the formation of Maillard reaction products during baking. The current result in similar to findings of other studies (Pereira et al, 2013;Adeola and Ohizua, 2018). The browning of the baked products increased with sweet potato flour, for example the BI value of RF biscuits was 87.87, which significantly lower than the value for 50% RF: 30% SPF: 20% SF (BI=176.31).…”
Section: Color Attributes Of Gluten-free Biscuitsupporting
confidence: 91%
“…Color is an important because it can arouse individual's appetite. It is one of the parameters used for process control during baking and roasting, because brown pigments appear as browning and caramelization reactions progress (Pereira et al, 2013).…”
Section: Color Attributes Of Gluten-free Biscuitmentioning
confidence: 99%
“…Color is an important attribute because it can arouse individual's appetite. It is one of the parameters used for process control during baking and roasting, because brown pigments appear as browning and caramelization reactions progress (Pereira, Correia, & Guine, ). The L*, a*, and b* values of the biscuit samples were lower for the topside than downside (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The color of the biscuits changed to dark brown from creamy yellow as the inclusion level of PPF and SPF increased. This may be due to the ingredient composition, air velocity in the oven, and red pigmentation resulting from the Maillard reaction or nonenzymatic browning which depends on the content of reducing sugars and amino acids or proteins on the surface, baking temperature, and time (Pereira et al., ). The current result is similar to the findings of other workers (Pereira et al., ).…”
Section: Resultsmentioning
confidence: 99%